Budaya Mitoni: Analisis Nilai- Nilai Islam dalam Membangun Semangat Ekonomi - Machmudah, Umi (el Harakah: Jurnal Budaya Islam, 2016)
Culture as the result of ideas, feelings and intention in Islam is the manifestation of worship. This paper is written through literary review that is completed with observation from some mitoni traditions. The culture form of ideas, activities and artifact is applied in 'mitoni'. It is a celebration on seventh month of pregnancy age. The activities done in mitoni are 1) bathing, 2) 'brojolan' ritual, 3) clothing change ritual, 4) prayer, 5) gift. Islamic values that inspire economic activities in mitoni are 1) thanksgiving that encourages people to be productive, 2) 'tafaa’ul' through prayer to be selective in consuming goods, 3) helping each others to manage the production cost, 4) implied education as all the activities are based on knowledge, 5) visitation to make connection through service distribution, 6) almsgiving through the gift that will maximize the production value, 7) reciting the verses of al-Quran and their meaning, some of which related to prosperity, 8) economic creativity, through the use of various apparatus and foods, bearing production activities. Budaya sebagai hasil dari cipta, rasa dan karsa manusia, dalam Islam merupakan manifestasi dari ibadah. Makalah ini ditulis melalui kajian pustaka dilengkapi dengan observasi dari beberapa acara mitoni. Wujud budaya yang berupa gagasan, kegiatan dan artefak yang teraplikasi pada budaya 'mitoni' 'Mitoni' adalah perayaan tujuh bulan usia kehamilan. Rangkaian mitoni adalah 1) siraman, 2) upacara brojolan, 3) upacara pergantian busana, 4) doa dan 5) 'mberkat'. Nilai-nilai Islam yang menyemangati aktivitas ekonomi dalam budaya 'mitoni' adalah: a) tasyakuran, mendorong orang untuk produktif 2) 'tafaa’ul' (optimisme) melalui doa, yang menjadi kekuatan untuk selektif dalam mengkonsumsi barang, 3) tolong menolong, yang berdampak pada penekanan biaya produksi, 4) pendidikan (pre natal) yang tidak terstruktur, menyebabkan penghematan biaya operasional, karena semua tindakan dilandasi ilmu pengetahuan, 5) silaturrahmi, berarti membuat jejaring untuk memperluas distribusi barang atau jasa. 6) sedekah melalui 'mberkat' akan memaksimalkan nilai produksi, 7) tilawah al-Quran dan tadabbur maknanya, yang sebagian berhubungan dengan kemakmuran, 8) kreatifitas ekonomi, melalui penggunaan berbagai piranti dan makanan, yang melahirkan aktivitas produksi.